The Importance Of The Role Of Parents In The Formation Of Children's Character Amidst The Rise Of Cases Of Violation By Minors - Nurhayati Nurhayati; Muya Syaroh Iwanda Lubis; Dea Ananda Putri; Muhammad Luthfi (Universitas Dharmawangsa Medan, 2024)
Parents play a very important role in the process of child personality development. The role of parents is to be aware of the child's condition and focus on understanding good examples of his character. Especially with the current rise in bullying cases, the role of parents is very important in shaping children's character so that they do not become victims or perpetrators. The reason for carrying out this investigation is the prevalence of bullying among minors, which is a serious problem and requires follow-up action. The aim of this research is to clarify the role of parents in developing children's character in responding to bullying. The method used in this research is qualitative method. Research shows that parents have a very important role in the development of a child's personality. Because, the first people who model their behavior are their parents. Parents can instill character in their children by setting an example, doing good deeds, communicating, and involving children in activities at home. Therefore, the character that parents instill in their children from an early age will make them more confident, strong and able to appear assertive in their environment. To combat bullying, parents must educate and strengthen their children to be fearless and self-confident, empowering them to choose friends at social gatherings and even to protect themselves and even seek revenge.